2009
DOI: 10.4049/jimmunol.0802986
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Formyl Peptide Receptor Family in Human NK Cells

Abstract: We determined the expression of the formyl peptide receptor (FPR) family and the functional roles of the FPR family in NK cells. All tested human NK cells express two members of the FPR family (FPR1 and FPR2). The expression of FPR3 was noted to occur in a donor-specific manner. The stimulation of NK cells with FPR family-selective agonists (fMLF (N-formyl-Met-Leu-Phe), MMK-1, F2L, and WKYMVm (Trp-Lys-Tyr-Met-Val-d-Met)) elicited cytolytic activity in resting NK cells, but not in IL-2-activated NK cells; the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 53 publications
2
54
0
1
Order By: Relevance
“…However, many chemotactic compounds are not chemokines but other types of proteins, peptides or lipids. The expression on NK cells of functional chemotactic receptors for lysophosphatidic acid [78], leukotrienes [79], histamine [80], formylated peptides [81] has been described. They seem to induce NK cell chemotaxis in vitro but their role in NK cell trafficking in vivo has not been investigated.…”
Section: Box 1 Other Gpcrsmentioning
confidence: 99%
“…However, many chemotactic compounds are not chemokines but other types of proteins, peptides or lipids. The expression on NK cells of functional chemotactic receptors for lysophosphatidic acid [78], leukotrienes [79], histamine [80], formylated peptides [81] has been described. They seem to induce NK cell chemotaxis in vitro but their role in NK cell trafficking in vivo has not been investigated.…”
Section: Box 1 Other Gpcrsmentioning
confidence: 99%
“…Since FPR1 has been reported to mediate phosphorylation of MAP kinases in various cell types, [22][23][24] we stimulated serumstarved HepG2 and Hep3B cells with 100 nM fMLF and determined MAPK phosphorylation at different time points. fMLF stimulated ERK1/2 phosphorylation with a maximum effect at 5 min.…”
Section: Fpr1 Mediates Mapk Activation In Hepatocellular Carcinoma Cellsmentioning
confidence: 99%
“…These receptors recognize a wide variety of structurally unrelated natural and synthetic ligands including the arylcarboxylic acid hydrazide AG-14, the cheno/deoxycholic acid CDCA/DCA, aspirinInternational Immunopharmacology 11 (2011) [55][56][57][58][59][60][61][62][63][64][65][66] triggered lipoxin (ALX), the LL-37 and CCL23β peptides, serum amyloid A (SAA) and the name-giving agonist peptide fMLP [26][27][28]. Seminal studies by Walter et al and other studies have identified the N-terminus derived AnxA1 peptide Ac.2-26 as a ligand for FPR1 [29][30][31].…”
Section: Introductionmentioning
confidence: 99%